Efficient generation of transgene-free human induced pluripotent stem cells (iPSCs) by temperature-sensitive Sendai virus vectors - Ban, Hiroshi; Nishishita, Naoki; Fusaki, Noemi; Tabata, Toshiaki; Saeki, Koichi; Shikamura, Masayuki; Takada, Nozomi; Inoue, Makoto; Hasegawa, Mamoru; Kawamata, Shin; Nishikawa, Shin-Ichi (Proceedings of the National Academy of Sciences - PNAS, 2011)
After the first report of induced pluripotent stem cells (iPSCs), considerable efforts have been made to develop more efficient methods for generating iPSCs without foreign gene insertions. Here we show that Sendai virus vector, an RNA virus vector that carries no risk of integrating into the host genome, is a practical solution for the efficient generation of safer iPSCs. We improved the Sendai virus vectors by introducing temperature-sensitive mutations so that the vectors could be easily removed at nonpermissive temperatures. Using these vectors enabled the efficient production of viral/factor-free iPSCs from both human fibroblasts and CD34+ cord blood cells. Temperature-shift treatment was more effective in eliminating remaining viral vector-related genes. The resulting iPSCs expressed human embryonic stem cell markers and exhibited pluripotency. We suggest that generation of transgene-free iPSCs from cord blood cells should be an important step in providing allogeneic iPSC-derived therapy in the future.